Antimigratory Evaluation from Curcumin-Derived Synthetic Compounds PGV-1 and CCA-1.1 on HCC1954 and MDA-MB-231 Cells - Novitasari, Dhania; Meiyanto, Edy; Kato, Jun-ya; Jenie, Riris Istighfari (Indonesian Society for Cancer Chemoprevention, 2022)
Earlier findings reported the anticancer-mediated activities of curcumin-modified compounds Pentagamavunone-1 (PGV-1) and Chemoprevention Curcumin Analog 1.1 (CCA-1.1) with several mechanisms including cell cycle arrest, reactive oxygen species (ROS) production, and cell migration disruption. Our study aims to evaluate the antimigratory activity of PGV-1 and CCA-1.1 on aggressive breast cancer cell lines (MDA-MB-231 and HCC1954 cells) and their effect on HER2 protein. The trypan blue exclusion method was conducted for the antiproliferative effect. The PGV-1 or CCA-1.1 effect on cell migration was determined by wound healing assay. Using gelatin zymography, we checked the secretion level of matrix metalloproteinase (MMP). We also evaluated the human epidermal growth receptor-2 (HER2) level after incubation with PGV-1 or CCA-1.1 in HCC1954 cells by western blot. Based on the antiproliferation assay, MDA-MB-231 and HCC1954 cells were sensitive to PGV-1 and CCA-1.1. MMP-2 was only observed in HCC1954 cells while MMP-9 was only observed in MDA-MB-231. Both PGV-1 and CCA-1.1 significantly suppressed MMP-9 activity in MDA-MB-231 cells. Moreover, PGV-1 inhibited HER2 protein levels in HCC1954 although it was not significant, whereas CCA-1.1 did not affect HER2 protein. This study strengthens the scientific evidence for PGV-1 and CCA-1.1 activities for future exploration as candidate chemotherapy with multitarget against breast cancer.Keywords: Curcumin analog, cell migration, MMP-9, HER2, breast cancer.